Pb210 dates of marine sediment core BC523 - Claire Susannah Allen; Victoria L Peck (PANGAEA, 2026)
The box core (BC) 523 was collected in 2008 from an inner shelf basin of Marguerite Bay, Antarctic Peninsula (67° 51.33 extquotesingle S; 68° 12.282 extquotesingle W) during research cruise JR179 aboard the RRS James Clark Ross. The chronology was established using the Constant Rate of Supply model of Pb210 measurements on the top 23 cm of sediment core. This research was supported by core funding from the Natural Environment Research Council to the British Antarctic Survey extquotesingles Palaeo Environment, Ice Sheets and Climate Change Program.